2021
DOI: 10.1111/jvs.12993
|View full text |Cite
|
Sign up to set email alerts
|

Similar successional development of functional community structure in glacier forelands despite contrasting bedrocks

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…We therefore had to compromise and selected the moraine with an age of 110 years as our youngest moraine. At each moraine, the vegetation was mapped (Greinwald et al, 2021b), and the soil physical characteristics were identified in 10, 30, and 50 cm depth (Hartmann et al, 2020b).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…We therefore had to compromise and selected the moraine with an age of 110 years as our youngest moraine. At each moraine, the vegetation was mapped (Greinwald et al, 2021b), and the soil physical characteristics were identified in 10, 30, and 50 cm depth (Hartmann et al, 2020b).…”
Section: Study Sitementioning
confidence: 99%
“…For the Brilliant Blue tracer experiments, three plots (1.0× 1.5 m) were selected on each moraine. To capture the spatial heterogeneity of the vegetation cover, the plots at each moraine were chosen along a gradient in vegetation complexity (Greinwald et al, 2021b). At each plot, species richness, root length density (RLD), vegetation cover, above-ground biomass (BM), and the slope were measured or estimated by Greinwald et al (2021a) (Table 1).…”
Section: Study Sitementioning
confidence: 99%
“…This measure was developed in the larger context of the interdisciplinary chronosequence study (e.g. Musso et al (2019), Maier et al (2020), Greinwald et al (2021b)) and is defined as a combination of vegetation cover and a measure of functional diversity. We chose the functional divergence as an index of functional diversity, which describes the variance of species traits in the community (Greinwald et al, 2021b).…”
Section: Plot Selection and Vegetation Complexitymentioning
confidence: 99%
“…Musso et al (2019), Maier et al (2020), Greinwald et al (2021b)) and is defined as a combination of vegetation cover and a measure of functional diversity. We chose the functional divergence as an index of functional diversity, which describes the variance of species traits in the community (Greinwald et al, 2021b). This index describes the functional similarity of communities in the multivariate niche space, and it has the advantage of not being correlated to vegetation cover.…”
Section: Plot Selection and Vegetation Complexitymentioning
confidence: 99%
See 1 more Smart Citation